Bio-jet fuel range in biofuels derived from hydroconversion of palm olein over Ni/zeolite catalysts and freezing point of biofuels/Jet A-1 blends. (1st June 2021) - Chintakanan, Pachara; Vitidsant, Tharapong; Reubroycharoen, Prasert; Kuchonthara, Prapan; Kida, Tetsuya; Hinchiranan, Napida
Graphical abstract: Highlights: Ni/NH4 -Beta catalyst was effective for producing high content of branched biofuels. 20.8 wt% Bio-jet yield with the highest iso-/n-alkanes ratio of 1.67 were obtained. Small Pt content and high H2 pressure gave high bio-jet yield with iso-/n-alkanes ratio > 1.00. Oxygenated and unsaturated compounds in liquid biofuels were successfully eleminated. Biofuel (iso-/n-alkanes ratio = 1.67)/Jet A-1 blend at 50/50 (v/v) provided Tf ca. −80 °C. Abstract: According to the regulation announced by International Air Transport Association to reduce greenhouse gas emissions, there are many attempts to produce bio-jet fuels from natural oils to replace, at least in part, the fossil fuels. However, bio-jet fuels usually suffer from poor cold flow properties. Hence, this research aimed to convert palm olein to bio-jet fuel range with high content of iso -alkanes via hydroconversion over nickel (Ni)/zeolite-based catalysts. The levels of liquid biofuels classified as bio-gasoline, bio-jet and green diesel, including the selectivity for chemical compositions were evaluated. Under 40 bar initial H2 pressure at 360 °C for 4 h, the use of Ni/NH4 -Beta catalysts (Ni content = 10 wt%) provided the maximum iso-/n-alkane ratio at 1.67 with a bio-jet yield of 20.8 wt%. The schematic reaction mechanism for this process was also proposed. The incorporation of platinum (Pt) into the Ni/NH4 -Beta catalysts to a Pt/(Pt + Ni) wt ratio of 0.24 increased the bio-jet yield to 28.7 wt% with iso-/n-alkane ratio of 1.02. Differential scanning calorimetry thermograms indicated that the freezing temperature (Tf ) of the biofuels decreased with increasing iso-/n-alkane ratio, where the Tf of the liquid biofuels with iso-/n-alkane ratio > 1.00 was not observed. For the biofuels/fossil jet fuel (Jet A-1) blends, the use of biofuels having iso-/n-alkane ratio of 1.67 could be blended with Jet A-1 up to 50/50 (v/v) and the Tf of the blended jet fuel was found at ca. −80 °C, which was lower than the limitation according to ASTM D1655-04a (−47 °C).